Joint exposure to various ambient air pollutants and incident heart failure: a prospective analysis in UK Biobank. - Wang, Mengying; Zhou, Tao; Song, Yongze; Li, Xiang; Ma, Hao; Hu, Yonghua; Heianza, Yoriko; Qi, Lu (2021)
AIMS: Little is known about the relation between the long-term joint exposure to various ambient air pollutants and the incidence of heart failure (HF). We aimed to assess the joint association of various air pollutants with HF risk and examine the modification effect of the genetic susceptibility.